PRICE DETERMINATION IN MOBILE PHONE TRADING TRANSACTIONS: AN ISLAMIC ECONOMICS PERSPECTIVE - Fatiha Sari (Jurnal Ilmiah Al-Tsarwah, 2026)
Pricing is an essential aspect of buying and selling activities that must uphold the principles of justice, honesty, and transparency in accordance with Islamic economics. This study aims to analyze the pricing mechanism, the pricing strategies implemented, and their conformity with the principles of Islamic economics. This study employed a qualitative field research approach. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman data analysis model. The findings indicate that pricing is determined based on distributor prices, distribution costs, and reasonable profit margins. The pricing strategies implemented include competitive pricing, discounts, bundling promotions, low-price add-on programs, purchase bonuses, and service quality improvement. These practices comply with the principles of Islamic economics by promoting justice, honesty, transparency, and public benefit (maslahah), while avoiding elements of riba (usury), gharar (uncertainty), tadlis (deception), and ihtikar (hoarding). The pricing strategies implemented by 88 Cellular Group are consistent with the principles of Islamic economics, as they are not solely profit-oriented but also promote fair and ethical business transactions. Business practitioners are encouraged to consistently uphold Islamic principles in pricing strategies to enhance consumer trust and foster sustainable business practices.